A comparison of calcium and phosphorus in components of fertile and size-matched unbanded Nile crocodile eggs. Issue 2 (10th December 2021) - Brown, GJ; Forbes, PBC; Myburgh, JG; Nöthling, JO
ABSTRACT: Research in other species suggests that the source of embryonic calcium (Ca) and phosphorus (P) for Crocodylus niloticus is likely yolk and shell. Using inductively coupled plasma optical emission spectroscopy (ICP-OES), the Ca and P concentration and content of 30 fertile eggs was determined within 10 days prior to anticipated hatching, and compared with those of size-matched unbanded eggs (eggs that failed to form an opaque band around the lesser circumference, indicative of presumed infertility). Shell contained the highest Ca concentration and content, followed by the foetus, followed by the intra-abdominal yolk. Foetal tissue had the highest P concentration and content, followed by intra-abdominal yolk. The Ca and P concentration of intra-abdominal yolk of foetuses in fertile eggs varied more widely than did the yolk of unbanded eggs, based on coefficient of variation. Ca concentration of fertile egg yolk was in some cases found to exceed that of the yolk of unbanded eggs, suggesting that Ca is stored there after being removed from the shell, however, yolk Ca content was consistently lower in fertile than in unbanded eggs, indicating net yolk Ca depletion. Yolk P concentration and content of fertile eggs was consistently lower than that of unbanded eggs, suggesting a net depletion of yolk P reserves, without replenishment. The Nile crocodile appears to follow the classic archosaurian pattern of Ca mobilisation, whereby the shell supplies the majority of foetal Ca, but the intra-abdominal yolk contains substantial Ca reserves for use by the hatchling. This study provides clinicians and researchers with information on sample collection and analysis of Nile crocodile egg and foetal tissue, provides baseline descriptive data on Ca and P concentration and content, discusses the effect of potential covariates on Ca and P concentration and content, and discusses the movement of Ca and P from reserves within the egg to the developing foetus.